A cross-sectional study on urogenital schistosomiasis in children; haematuria and proteinuria as diagnostic indicators in an endemic rural area of Nigeria (2014)
Background: Rapid and accurate diagnosis is necessary for the management of schistosomiasis in endemic areas. Objective: To assess the burden of urogenital schistosomiasis and the diagnostic efficiency of morbidity indicators of the disease in an endemic rural community of Nigeria. Methods: A cross-sectional school-based study was conducted. Urine samples of 487 pupils were screened microscopically for S. haematobium and tested for haematuria and proteinuria using chemical reagent strips. Results: The prevalence and intensity of infection were 57.1% and 45.0 eggs/10 mL urine respectively. Prevalence of infection in male (54.1%) and female (60.3%) individuals showed no significant variation (P>0.05). However, prevalence of infection was age dependent with those in age groups 3-5 and 12-14 years having the least and highest prevalence of infection respectively (P<0.05). Microhaematuria and proteinuria varied significantly with ages of the pupils with least (14.0, 40.0%) and highest (60.0, 80.0%) prevalence recorded in age groups 3-5 and 15-19 years respectively (P<0.05). Proteinuria showed higher sensitivity (80.3%) compared to microhaematuria (73.3%). Conclusion: Schistosomiasis is highly endemic in the study area and the use of microhaematuria and proteinuria for mapping the infected population prior treatment could be adopted.